Study of structural, optical and photocatalytic activity of Sm and Ni doped BiFeO3 (BFO) and BFO@ZnO nanostructure. (2020) - Sahni, Mohit; Kumar, Dharmesh; Chauhan, Sunil; Singh, Munendra; Kumar, Naresh
Abstract: Sol-gel synthesized Sm and Ni substituted bismuth ferrite (Bi1−x Smx Fe1−x Nix O3, x = 0.04) particles were summed up with ZnO by reflexing method. X-ray diffraction and field emission scanning electron microscopy were used for structural and microstructural studies. The XRD outcome exposed the coating of ZnO on distorted rhombohedral (R3c) structured Sm and Ni substituted BiFeO3 . The particle size of Sm and Ni substituted BiFeO3 nanoparticles were estimated to be 50–90 nm. The grain size and surface morphology of Bi1−x Smx Fe1−x Nix O3 (x = 0.04) @ZnO nano composite was studied from FESEM micrographs. Elemental analysis was done by EDX. The energy band gap was found to be ∼ 2.00 eV for Bi0.96 Sm0.04 Fe0.96 Ni0.04 O3 and ∼2.35 eV for ZnO (from UV–VIS spectra). It was detected that the optical absorption was higher for Bi0.96 Sm0.04 Fe0.96 Ni0.04 O3 @ZnO nano composite than Bi0.96 Sm0.04 Fe0.96 Ni0.04 O3 nanoparticles. The photocatalytic degradation efficiency for Bi0.96 Sm0.04 Fe0.96 Ni0.04 O3 @ZnO nano composite was found to be higher than Bi0.96 Sm0.04 Fe0.96 Ni0.04 O3 nanoparticles.